THE DEVELOPMENT OF ENTREPRENEURIAL SKILLS AMONG STUDENTS OF AVERAGE PROFESSIONAL EDUCATIONAL INSTITUTIONS: THE EXPERIENCE OF THE TOMSK REGION - N V Belyakov; A P Glinushkin (Universitas Brawijaya, 2019)
The paper aims to define the solution to the problem of developing entrepreneurial skills among students. Based on the experience of developing and shaping entrepreneurial skills and professional competencies in the Tomsk region, it is proposed to organize educational activities in two areas: the actual educational (introduction of academic disciplines) and extracurricular (participation in competitions and programs of entrepreneurial projects).